The Influence of Competence, Physical Work Environment and Benefits on the Performance of the Civil Service Apparatus (ASN) at the Johor Medan Sub-District Office - sinto sinto; Aisyah Harahap; Nur Ainun (Jurnal Ekonomi LLDIKTI Wilayah 1 (JUKET), 2021)
The purpose of this research is to identify the impact of Competence, Physical Activity Areas, and Allowances on the achievements of the State Civil Apparatus (ASN) at the Johor Medan Sub-District Office. The results of this research prove that partially the Competence variable (X1) has a positive and significant influence on the ability of the State Civil Apparatus (Y), with a count of 4.218 and a degree of significance of 0.000, which is smaller than 0.05 in a partial way. Physical Work Environment (X2) has a positive and significant impact on the ability of the State Civil Apparatus (Y), with a count of 5.028 and an essential degree of 0.000, less than 0.5, with partial benefits (X3) affecting positively and significantly to the ability of the State Civil Apparatus (Y), with a count of 6.272 and a significant degree of 0.000 less than 0.05. On the other hand, simultaneously, Competence (X1), Physical Work Environment (X2), and Allowances (X3 ) has a positive and significant impact on the ability of the State Civil Apparatus at the Johor Area Camat Office, with a Fount of 220, 805 and a substantial degree of 0, 0 00 is less than 0.05